Isolation of Staphylococcus aureus clumping factor. - Espersen, F (1985)
Immunochemically identical components were isolated from water-soluble phases of five Staphylococcus aureus strains by affinity chromatography on fibrinogen-linked Sepharose 4B. The elution was performed with 1 M MgCl2. The component could be isolated from sonicated preparations of whole cells, cell walls, and extracellular products of S. aureus but not from sonicated preparations of staphylococcal L-forms or from Staphylococcus epidermidis. Investigations of the eluted component by immunoelectrophoresis and Western blot analysis by use of different polyspecific antibodies to S. aureus raised in rabbits revealed only one immunoprecipitate or one band. By means of gel filtration on Sepharose CL 6B and sodium dodecyl sulfate-polyacrylamide gel electrophoresis a molecular mass of 420,000 and 360,000 was found, respectively. Chemical analysis showed a carbohydrate content of about 20% by weight. By crossed immunoelectrophoresis the isolated component was demonstrated to bind to human fibrinogen. The finding that this purified component inhibited the fibrinogen-induced clumping of staphylococci strongly suggests that the component is the S. aureus clumping factor.